Addition of Butyric Acid and Lauric Acid Glycerides in Nursery Pig Feed to Replace Conventional Growth Promoters - Ficagna C.A.* (2024)
© 2024 by the authors.(1) Background: This study determined whether adding butyric acid and lauric acid glycerides in nursing pigs’ feed would improve growth performance, proteinogram, biochemical parameters, and antioxidant status. (2) Methods: Ninety male pigs were divided into five groups with six repetitions per group: NC, negative control (no additive); TRI-BUT, addition of tributyrin in the basal ration; MDT-BUT, addition of mono-, di-, and triglycerides of butyric acid in the basal feed; MDT-LAU, the addition of mono-, di-, and triglycerides of lauric acid in the basal feed; and PC, positive control (addition of gentamicin in the basal feed). (3) Results: PC, TRI-BUT, and MDT-LAU resulted in a high average daily WG from days 1 to 39 (p < 0.01). MDT-LAU, MDT-BUT, and PC resulted in a greater feed:gain from days 1 to 39 than the NC (p = 0.03). Great concentrations of the gamma globulin fraction in all groups were observed than in the NC (p = 0.01). Ceruloplasmin, haptoglobin, and C-reactive protein concentrations were lower in all groups than in the NC (p < 0.05). Higher serum glutathione S-transferase activity was observed in the TRI-BUT and MDT-BUT than in the PC (p = 0.04). (4) Conclusions: The addition of butyric acid and lauric acid glycerides in the diet of pigs in the nursery phase can replace growth promoters since the products improve the growth performance, reduce acute-phase proteins, and increase gamma globulin concentrations.